Constraints to Dark Matter from Inert Higgs Doublet Model. (28th February 2016) - Díaz, Marco Aurelio; Koch, Benjamin; Urrutia-Quiroga, Sebastián
Abstract : We study the Inert Higgs Doublet Model and its inert scalar HiggsH as the only source for dark matter. It is found that three mass regions of the inert scalar Higgs can give the correct dark matter relic density. The low mass region (between 3 and 50 GeV) is ruled out. New direct dark matter detection experiments will probe the intermediate (between 60 and 100 GeV) and high (heavier than 550 GeV) mass regions. Collider experiments are advised to search forD ± → H W ± decay in the two jets plus missing energy channel.